Using international large-scale assessment for learning: Analyzing U.S. students’ geometry performance in TIMSS - Liu, Jinqing; Zhou, Lili; Bharaj, Pavneet Kaur; Zhou, Da; Lo, Jane-Jane (JRAMathEdu (Journal of Research and Advances in Mathematics Education), 2024)
The data from international large-scale assessments, such as The Trends in International Mathematics and Science Study (TIMSS), is often designed and used as an assessment of learning rather than an assessment for learning. This research employed TIMSS 2011 data, focusing on the geometric performance of fourth-grade students in the United States,  to demonstrate how large-scale assessments can be utilized qualitatively to identify students' learning challenges, providing valuable insights to inform geometry teaching practices. Using van Hiele’s levels of geometric thinking as a guiding framework, the 24 released geometry items were analyzed to identify students’ struggle points in geometry nationwide. Our analysis revealed that students performed well on tasks that were visual, contextually grounded, and had clearly defined manipulative expectations.. However, students needed further support to solve items requiring a deep understanding of geometrical concepts, such as finding the perimeter of a square. Additionally, students excelled at solving tasks involving the identification of relative positions of objects on a map and recognizing lines of symmetry in regular shapes. However, they struggled with measurement-related tasks. Our analysis also identified a range of item features that might cause difficulties that impacted the way students responded to these items. Instructional implications for elementary mathematics education are discussed.